Poetry in Late Byzantium - Kubina, Krystina, (Late Antiquity and Medieval Studies E-Books Online, Collection 2024., 2024)
The late Byzantine period (thirteenth to fifteenth centuries) was marked by both cultural fecundity and political fragmentation, resulting in an astonishingly multifaceted literary output. This book addresses the poetry of the empire's final quarter-millennium from a broad perspective, bringing together studies on texts originating in places from Crete to Constantinople and from court to school, treating topics from humanist antiquarianism to pious self-help, and written in styles from the vernacular to Homeric language. It thus offers a reference work to a much-neglected but rich textual material that is as varied as it was potent in the sociocultural contexts of its times. Contributors are Theodora Antonopoulou, Marina Bazzani, Julián Bértola, Martin Hinterberger, Krystina Kubina, Marc D. Lauxtermann, Florin Leonte, Ugo Mondini, Brendan Osswald, Giulia M. Paoletti, Cosimo Paravano, Daniil Pleshak, Alberto Ravani, and Federica Scognamiglio.